EXPLORING ETHICAL VIEWS IN “KABUSNAMA”: UNRAVELING THE LEGACY OF UNSURUL-MAOLIY KAYKOVUS - Rahimova Shoira Adilbekovna, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The study delves into the historical and philosophical exploration of the spiritual culture of thinkers, emphasizing the significance of understanding their philosophical legacies. In times of socio-political and cultural transformations, the breakdown of traditional norms prompts a reevaluation of values, necessitating the exploration of past thinkers to guide modern society’s ideological development. A focal point is the revival of universal values such as humanism, justice, mercy, compassion, friendship, and mutual understanding to address the contemporary spiritual crisis. The article argues for a deep examination of the ethical views of historical thinkers, particularly Unsurul-Maoliy Kaykovus (1020-1083). Despite being part of the influential medieval East thinkers, Kaykovus’s ethical ideas remain inadequately explored. The study proposes that understanding his ethical views is crucial for comprehending the development of practical philosophy and bridging the historical gap in ethical thought. Highlighting the scarcity of systematic research on Kaykovus’s ethical ideas, the article emphasizes the need for a scientific approach. Kaykovus, a prominent figure in medieval East philosophy, expressed his social and ethical views in “Kabusnama” a moral and didactic literary work. The study of “Kabusnama” not only sheds light on Kaykovus’s worldview but also contributes to understanding socio-ethical thought in the 11th century and its impact on the Near and Middle East.